FACTORS THAT AFFECT THE INCIDENCE OF HYPERTENSION IN PREGNANCY IN THE WORKING AREA OF THE FISH MARKET HEALTH CENTER IN BENGKULU CITY - Mariati mariati; Yemi Rahmadania; Eliana (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
Hypertension during pregnancy is a common obstetric complication and a major contributor to both maternal and fetal morbidity and mortality. This study aimed to identify factors affecting the occurrence of hypertension in pregnancy within the Pasar Ikan Community Health Center’s service area. Employing an observational analytical design with a cross-sectional approach, the study involved 50 pregnant women in their first and second trimesters, selected through total sampling. The findings revealed that 32% of the participants experienced hypertension during pregnancy. Significant correlations were found between maternal age and hypertension, as well as between caffeine intake and hypertension occurrence. Conversely, gravidity showed no significant relationship with hypertension incidence. Caffeine consumption emerged as the most influential factor, with a sevenfold greater impact compared to other variables. It is advised to enhance educational efforts targeting pregnant women about their consumption habits and the associated hypertension risks.